PENGUATAN UPAYA TESTING DAN TRACING DALAM MENGHADAPI PANDEMI COVID 19 DENGAN PELAYANAN PEMERIKSAAN PCR SARS COV 2 UNTUK MASYARAKAT KOTA CIMAHI (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
The Covid-19 pandemic has spread all over the world. Covid-19 can be transmitted through frequent contact with one's body or other people. One of the easy and effective steps recommended by the World Health Organization to prevent the spread of Covid-19 is hand washing with soap (CTPS) using airflow. The purpose of this activity is to increase the knowledge of 80% of students regarding Hand Washing with Soap (CTPS). This outreach activity was carried out at SDN No. 129 Inpres Bontoloe, Galesong District, Takalar Regency, and was attended by 15 students. The method used is a lecture coupled with playing games and singing the steps of Washing Hands with Soap (CTPS). The results of the pre-test and post-test showed that there was an increase in the average knowledge from 8.93 to 9.93. The results of the Wilcoxon test analysis showed that the p-value was 0.002
Keywords: Cimahi city; interprofessional collaboration; covid-19 pandemic; PCR examination